The Adopted Strategic Management Practices on Governance of LGAs in Tanzania - Pandisha, Haghai; Kombe, Wilbard; Kayunze, Kim (Journal of Public Policy and Administration, 2023)
Purpose: Local Government Authorities are constantly implementing activities directed from central government by means of decentralization to enhance governance in resource allocation and service deliverance. This has made councils to engage in SMPs in order to continue and achieve their targeted goals. This study aims to explore Strategic Management Practices adopted by Local Government Authorities in Tanzania. Methodology: The study adopted diagnostic survey design by taking into account all steps involved in survey studies to obtain important data concerning Strategic Management Practices adopted in Local Government Authorities. Both simple and purposive sampling were employed to determine the study sample of 351 staff council who participated in implementation of Strategic Management Practices. Questionnaire, interviews and Focus Group Discussions were used to collect the information from the respondents. Descriptive analysis was used to compute frequencies and percentage, while content analysis was used to analyze the main themes from key informants. The study selected Mufindi District Council as a case study to explore the Strategic Management Practices adopted. Findings: Finding of the study found councils undertaking situational analysis, formulation of strategic plan and performance review. Furthermore, finding revealed that councils are equipped with different strategic models in developing strategic plan particularly SWOT analysis and balanced scorecard. It was further found that management, institutional and resource factors have significantly influenced the councils' decision to adopt SMPs through strategic models. Unique Contribution to Theory, Practice and Policy: The study recommends that successfully strategy implementation can be achieved when councils allocates all required resources with effective monitoring of the activities.